Lithium ion battery
By adjusting the R angle of aluminum plastic film concave and adding additive A to the electrolyte, the problem of easy deformation and circulation stability of the high -expansion of the silicon -based negative pole material in the electrolytes, and the long cyclic expansion performance of the lithium ion battery and the performance of the lithium -ion battery Circulation stability improvement.
Patent Information
- Application Number
- CN202411741221.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-21
AI Technical Summary
The high expansion of the silicon-based negative electrode material during the cycle charging and discharge process leads to the fracturing of the negative electrode active layer and deteriorating the bonding performance, which leads to the easy deformation of lithium-ion batteries and the reduction of cycle stability.
By adjusting the R angle of the aluminum plastic film concave film, it matches the silicon carbon negative material of the appropriate particle size size, and adds additive A to the electrolyte to improve the long cyclic expansion performance and cycle stability of the lithium ion battery.
It effectively reduces the risk of battery deformation due to the high expansion characteristics of the silicon anode, and improves the long-cycle expansion performance and cycle stability of lithium-ion batteries.
Smart Images

Figure CN119340337A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery. Background Art
[0002] Silicon-based negative electrode materials have become the most promising negative electrode materials that can replace graphite due to their high gram capacity and high stability. However, due to the high expansion problem of silicon negative electrode containing silicon-based negative electrode materials during the cyclic charge and discharge process, the negative electrode active layer is easily broken and the bonding performance between the negative electrode active layer and the negative electrode current collector becomes poor. In addition, as the expansion continues to release, the thickness of the lithium-ion battery cell continues to increase, and the aluminum-plastic film covering the battery cell is prone to damage, which makes the lithium-ion battery easy to deform and the cycle stability decreases. Summary of the invention
[0003] Based on the above problems, the present invention provides a lithium ion battery, which can reduce the risk of easy deformation of the battery in the late cycle due to the high expansion characteristics of the silicon negative electrode, and improve the long-cycle expansion performance and cycle stability of the lithium ion battery.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] A first aspect of the present invention provides a lithium-ion battery, comprising a battery cell and an aluminum-plastic film coated on the outside of the battery cell; the battery cell comprises a negative electrode, the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon negative electrode material;
[0006] The average particle size of the silicon-carbon negative electrode material is X1 μm, 5 μm≤X1 μm≤15 μm;
[0007] The concave film R angle of the aluminum-plastic film is X2 mm, 0.01 mm ≤ X2 mm ≤ 3 mm;
[0008] Among them, 0.05≤X2 / X1≤0.15.
[0009] A second aspect of the present invention provides an electrochemical device, wherein the electrochemical device comprises the lithium ion battery according to the first aspect of the present invention.
[0010] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0011] The present invention adjusts the R angle of the concave film of the aluminum-plastic film to match the silicon-carbon negative electrode material with a suitable particle size, thereby reducing the risk of easy deformation of the battery in the late cycle due to the high expansion characteristics of the silicon negative electrode and improving the long-cycle expansion performance and cycle stability of the lithium-ion battery.
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 A schematic diagram of the concave R angle of an aluminum-plastic film provided by an embodiment of the present invention;
[0014] Figure 2 A schematic diagram of a method for measuring the concave R angle of an aluminum-plastic film provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0015] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0016] A first aspect of the present invention provides a lithium-ion battery, comprising a battery cell and an aluminum-plastic film coated on the outside of the battery cell; the battery cell comprises a negative electrode, the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon negative electrode material;
[0017] The average particle size of the silicon-carbon negative electrode material is X1 μm, 5 μm≤X1 μm≤15 μm;
[0018] The concave film R angle of the aluminum-plastic film is X2, 0.01 mm ≤ X2 mm ≤ 3 mm;
[0019] Among them, 0.05≤X2 / X1≤0.15.
[0020] Silicon-carbon negative electrode materials have high expansion characteristics. The expansion is continuously released during the cycle, causing the thickness of the lithium-ion battery to continue to increase. The larger the particle size of the silicon-carbon negative electrode material, the more obvious the expansion. Therefore, a matching aluminum-plastic film is needed to alleviate the space compression caused by high expansion, ensuring that the aluminum-plastic film does not break while having a certain binding effect.
[0021] The present invention adjusts the design parameters in the stamping process so that the R angle of the aluminum-plastic film concave film is within a suitable range, which can effectively alleviate the space compression caused by high expansion, and match it with a silicon-carbon negative electrode material of a suitable particle size, satisfying 0.05≤X2 / X1≤0.15, which can reduce the risk of easy deformation of the battery in the later stage of the cycle due to the high expansion characteristics of the silicon negative electrode, thereby effectively improving the long-cycle expansion performance and cycle stability of the lithium-ion battery. In a specific embodiment, 0.07≤X2 / X1≤0.12.
[0022] In the present invention, the average particle size of the silicon-carbon negative electrode material is X1μm, 5μm≤X1μm≤15μm, for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm. The average particle size X1 of the silicon-carbon negative electrode material can be obtained by taking the average value after testing with a particle size tester. The test method is: using Malvern MS3000, setting the test conditions as: refractive index 2.1, absorptivity 1.0, shading 8-12%, dispersant using water (or ethanol), stirring rate 2500rpm, testing 3 times the average value, where the D50 value is the average particle size of the silicon-carbon negative electrode material particles. In a specific embodiment, 7μm≤X1μm≤12μm.
[0023] In the present invention, the concave film R angle of the aluminum-plastic film is X2 mm, 0.01mm≤X2≤3mm, for example, 0.01mm, 0.02mm, 0.03mm, 0.04mm, 0.05mm, 0.06mm, 0.07mm, 0.08mm, 0.09mm, 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm, 2.5mm, 2.6mm, 2.7mm, 2.8mm, 2.mm, 3mm. The schematic diagram of the concave film R angle of the aluminum-plastic film is as follows: Figure 1 As shown, after the aluminum-plastic film undergoes the stamping process, a downwardly concave aluminum-plastic film structure, i.e., a concave film, is formed, and the projection shape of the concave film in the stamping direction is designed to be a rectangle based on the shape of the battery cell structure. The concave film R angle is the radius of the fillet formed by the edges of the four corners of the concave film when the concave film is rectangular (the fillet radii of the four corners are measured separately, and then the average value is taken, which is the concave film R angle); wherein the fillet radius can be quickly measured by an R gauge, and the specific measurement method is as follows: Figure 2 As shown, Figure 2A schematic diagram of a method for measuring the R angle of a concave film of an aluminum-plastic film provided by an embodiment of the present invention, first, an extension line is made along the edge of one of the corners, the two extension lines intersect at point C, point A and point B are the fillet starting points of the edges on both sides, then a perpendicular line of the edge extension line is made through point A, and a perpendicular line of another edge extension line is made through point B, the two perpendicular lines intersect at point D, point D and point C are connected, the intersection of DC and the fillet edge is point E, the distance between point D and point E is the fillet radius of the corner, the measuring method of the fillet radius of other corners is basically the same, the fillet radius of the four corners is measured respectively, and the average value is obtained, which is the R angle of the concave film. The R angle of the concave film can directly affect the quality and performance of the final product. In a specific embodiment, 0.5mm≤X2 mm≤1.5mm.
[0024] When the concave R angle of the aluminum-plastic film is too large, the expansion margin provided by the edge of the battery cell is very small, and the aluminum-plastic film will be stretched beyond its upper limit during the cyclic expansion process, causing the aluminum-plastic film to easily break. When the concave R angle of the aluminum-plastic film is too small, the space between the aluminum-plastic film and the battery cell is too large, and the restraint on the battery cell in the early stage of charging and discharging is too small, which can easily cause the battery cell to be in an unrestrained state and deform. Therefore, it is necessary to reasonably control the size of the concave R angle of the aluminum-plastic film to match the appropriate particle size of the silicon-carbon negative electrode material to avoid damage to the aluminum-plastic film while improving the cycle stability of the battery and reducing the deformation risk of lithium-ion batteries.
[0025] In summary, the present invention can reduce the risk of easy deformation of the battery in the later stage of the cycle due to the high expansion characteristics of the silicon negative electrode by reasonably regulating the R angle of the concave film of the aluminum-plastic film and matching it with a silicon-carbon negative electrode material with a suitable particle size, and can maximize the high gram capacity characteristics of the silicon negative electrode, thereby improving the energy density of the lithium-ion battery and ensuring that the lithium-ion battery has excellent long-cycle expansion performance and cycle stability.
[0026] In the present invention, the lithium ion battery further comprises an electrolyte, and the electrolyte comprises an additive A, and the structural formula of the additive A is shown in formula (1):
[0027]
[0028] Wherein, the value of n is 1-3 (for example, 1, 2, 3, n is an integer), R is independently selected from halogen (F, Cl, Br, I, preferably F), substituted or unsubstituted C1-C3 alkyl (C1-C3 alkyl includes -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2), and when substituted, the substituent of the C1-C3 alkyl is halogen (F, Cl, Br, I).
[0029] In a preferred embodiment, the substituent of the C1-C3 alkyl group is F.
[0030] Additive A can be anchored to the surface of silicon-carbon negative electrode material particles in the negative electrode system mixed with silicon-carbon negative electrode materials during the formation stage to generate an interface layer rich in magnesium-silicon alloy. The generated magnesium-silicon interface layer can improve the transmission rate of homogenized lithium ions, which is beneficial to improving the fast charging performance of the negative electrode system mixed with silicon-carbon negative electrode materials, and reducing the lithium insertion energy barrier of silicon-carbon negative electrode material particles, thereby helping to improve the fast charging capacity and rate performance of lithium-ion batteries. On the other hand, the metal-rich interface inner layer can improve the defect of poor conductivity of silicon-carbon negative electrode materials, making the organic-inorganic interface layer generated under high potential more stable and dense, thereby helping to improve the stability of the negative electrode interface, inhibiting the matching of R angle and particle size may lead to a decrease in the stability between silicon-carbon negative electrode material particles, reducing the continuous intensification of side reactions during the cycle, thereby reducing the adverse effects of side reactions on the cycle stability of lithium-ion batteries, and reducing the conductivity defects of silicon-carbon negative electrode materials, effectively improving the long-cycle stability of silicon negative electrodes, reducing the side reactions of silicon negative electrodes and improving the cycle expansion performance of lithium-ion batteries.
[0031] In a specific embodiment, the additive A comprises at least one of the following compounds;
[0032]
[0033] In the present invention, based on the total mass of the electrolyte, the mass content of the additive A is X3 wt%, 0.5wt%≤X3 wt%≤6wt%, for example, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%. In a specific embodiment, 0.7wt%≤X3wt%≤3wt%.
[0034] In the present invention, the mass content of element Si in the negative electrode active material is X4wt%, 0.5wt%≤X4wt%≤30wt%, for example, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%; in a specific embodiment, 1wt%≤X4wt%≤20wt%.
[0035] Further, in the present invention, 0.07≤X3 / X4≤0.55, for example, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55. In a specific embodiment, 0.1≤X3 / X4≤0.4.
[0036] Additive A has an anchoring film-forming effect on the silicon-carbon negative electrode material and can improve the stability of the interface of the silicon-carbon negative electrode material. When the content of additive A and silicon element in the negative electrode satisfies 0.07≤X3 / X4≤0.55, the long cycle effect of the lithium-ion battery can be further improved and the deformation of the battery can be suppressed; for example, when the ratio of X3 / X4 is less than 0.05, the amount of additive A does not match the blending amount of silicon-carbon negative electrode material in the silicon negative electrode, and the amount of additive A is insufficient to protect the silicon negative electrode interface. The side reaction continues to intensify during the cycle, and the stability of the silicon-carbon negative electrode material interface decreases, which is easy to deteriorate the long cycle performance and expansion performance of the lithium-ion battery; when the ratio of X3 / X4 is greater than 0.55, the mass content of additive A in the negative electrode active material is seriously excessive, which will cause the accumulation of additives on the surface of the silicon-carbon negative electrode material and other negative electrode active materials, increase the thickness of the magnesium-silicon interface layer formed, increase the difficulty of lithium ion transmission, and make the lithium insertion depth of the silicon negative electrode not reach the expected depth. The interface polarization continues to increase due to the continuous formation of SEI film during the charge and discharge process, thereby accelerating the capacity decay of the lithium-ion battery and affecting the long cycle performance of the lithium-ion battery. Therefore, the protective effect of the magnesium-silicon interface layer on the silicon-carbon negative electrode material can be improved by adjusting the ratio of the mass content X3 of the additive A to the mass content X4 of the silicon-carbon negative electrode material, thereby improving the stability of the interface of the silicon-carbon negative electrode material and improving the long cycle performance of the lithium-ion battery. Among them, the mass content ratio of the element Si in the negative electrode active material can be calculated by performing an EDS surface scan analysis on the negative electrode coating formed by the negative electrode active material.
[0037] In the present invention, the aluminum-plastic film comprises a first polymer layer close to the battery core, a second polymer layer away from the battery core, and an aluminum layer located between the first polymer layer and the second polymer layer.
[0038] In a specific embodiment, the thickness of the second polymer layer is 20μm-30μm, for example, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm. In a preferred embodiment, the thickness of the second polymer layer is 22μm-28μm. In a specific embodiment, the second polymer layer includes a polyamide compound, such as nylon (polyamide fiber). The main function of this layer is to protect the middle aluminum layer from being scratched by the outside world and reduce the damage to the battery cell structure caused by external factors such as collisions.
[0039] In a specific embodiment, the thickness of the aluminum layer is 35 μm-45 μm, for example, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm, 40 μm, 41 μm, 42 μm, 43 μm, 44 μm, 45 μm. In a preferred embodiment, the thickness of the aluminum layer is 37 μm-43 μm. The intermediate aluminum layer can effectively prevent oxygen and moisture from invading the battery core structure, thereby protecting the cycle performance and cycle life of the battery.
[0040] In a specific embodiment, the thickness of the first polymer layer is 40 μm-50 μm, for example, 40 μm, 41 μm, 42 μm, 43 μm, 44 μm, 45 μm, 46 μm, 47 μm, 48 μm, 49 μm, 50 μm. In a preferred embodiment, the thickness of the first polymer layer is 42 μm-48 μm. In a specific embodiment, the first polymer layer includes a polypropylene compound, such as polypropylene (PP), which can prevent the leaked electrolyte from corroding the aluminum layer.
[0041] The second polymer layer of the outer layer mainly plays a protective role and has heat resistance, wear resistance and puncture resistance. When the thickness of this layer is set between 20μm-30μm, it can provide better mechanical strength, but it may increase the flow resistance of the material during stamping, causing the material at the R corner of the die to become thinner, affecting the tensile strength of the aluminum-plastic film in the later stage of cyclic expansion. Therefore, it is necessary to control its thickness within a suitable range, which can improve the tensile strength of the material at the R corner of the die, making it more suitable for silicon negative electrodes with high expansion characteristics, thereby improving the long-cycle expansion performance and cycle stability of lithium-ion batteries.
[0042] The thickness of the aluminum layer directly affects the overall toughness and formability of the aluminum-plastic film. An overly thick aluminum layer will increase the difficulty of stamping, which may cause the die R angle X2 to be unable to be adjusted to the appropriate range, increasing the difficulty of the process, and will also make the material at the die R angle thinner, which is prone to cracking.
[0043] The inner first polymer layer is the part that is in direct contact with the battery cell. It is usually made of materials such as polypropylene (PP) and has a thickness in the range of 40μm-50μm. The thickness of the first polymer layer has an important influence on the electrolyte resistance. A thicker inner first polymer layer can improve the chemical corrosion resistance of lithium-ion batteries, but it may also increase stress concentration during stamping, especially in the material at the R corner of the die. Therefore, it is necessary to control the thickness of the inner first polymer layer within a suitable range to ensure the tensile strength and applicability of the R corner of the aluminum-plastic film, improve the high expansion problem of the silicon negative electrode, and enhance the long-cycle expansion performance and cycle stability of lithium-ion batteries.
[0044] In the present invention, the electrolyte further includes lithium difluorophosphate.
[0045] By adding the additive lithium difluorophosphate to the electrolyte, the cycle performance of the silicon negative electrode system can be further improved in combination with additive A. Additive A can generate a low-impedance stable interface film on the positive electrode side, inhibiting the transfer of high-voltage byproducts and transition metals on the positive electrode side to the negative electrode side. The silicon negative electrode is extremely sensitive to byproducts and transition metals. The suspended functional groups on the surface of the silicon-carbon negative electrode material and the byproducts generated by the reaction with the byproducts and transition metals hinder the transfer of lithium ions on the silicon negative electrode surface and deteriorate the cycle performance. The addition of the additive lithium difluorophosphate can generate a stable low-impedance interface film at the silicon negative electrode, which is beneficial to the ion transfer of lithium ions at the negative electrode interface of the silicon-carbon negative electrode material, and the fluorine-phosphorus interface film generated by it is more stable and has better toughness. Therefore, when used together with additive A, the cycle performance of lithium-ion batteries in the silicon negative electrode system can be significantly improved.
[0046] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the lithium difluorophosphate is 0.1wt%-1wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%. In a preferred embodiment, the mass content of the lithium difluorophosphate is 0.2wt%-0.6wt%.
[0047] In the present invention, the electrolyte also includes fluoroethylene carbonate (FEC). By adding FEC to the electrolyte, the long-cycle stability and storage performance of the silicon negative electrode can be further improved with additive A. FEC has an excellent film-forming effect on the silicon negative electrode and can stabilize the silicon negative electrode interface. Additive A generates a new alloy layer on the surface layer of the silicon-carbon negative electrode material, which improves the lithium ion transmission effect of the silicon-carbon negative electrode material. The silicon-carbon negative electrode material can be doubly protected by the stable alloy layer and the stable interface SEI. The combination can significantly improve the stability of the silicon-carbon negative electrode material and significantly improve the long-cycle performance and rate performance of the lithium-ion battery.
[0048] In a specific embodiment, based on the total mass of the electrolyte, the mass content of the fluoroethylene carbonate is 7wt%-20wt%, for example, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%. In a preferred embodiment, the mass content of the fluoroethylene carbonate is 10wt%-17wt%.
[0049] In the present invention, the thickness of the negative electrode sheet is 45 mm to 80 mm. It should be noted that the thickness of the negative electrode sheet refers to the total thickness of the negative electrode current collector and the negative electrode active coating on both sides thereof.
[0050] In the present invention, the electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalate borate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxalato)phosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methyl, and lithium bis(trifluoromethylsulfonyl)imide.
[0051] In the present invention, the electrolyte further includes an organic solvent, and the organic solvent includes at least one of carbonate and / or carboxylate.
[0052] In a specific embodiment, the carbonate includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0053] In a specific embodiment, the carboxylate includes at least one of propyl acetate, n-butyl acetate, isobutyl acetate, n-pentyl acetate, isopentyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate, and n-butyl ethyl acetate.
[0054] In the present invention, the electrolyte further includes other additives, and the other additives include at least one of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, ethylene sulfate, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, sebaconitrile, decanedinitrile, 1,3,6-hexanetricarbonitrile, glycerol trinitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,3-propane sultone, and allyl-1,3-sultone.
[0055] In the present invention, the battery cell includes a positive electrode, and the positive electrode may include a layered lithium composite oxide with the chemical formula Li (1+x) Ni y Co z M (1-y-z) O2, where -0.1 ≤ x ≤ 1; 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and 0 ≤ y + z ≤ 1; where M is one or several of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.
[0056] In the present invention, the negative electrode active material may further include a carbon-based negative electrode material, where the carbon-based negative electrode material includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.
[0057] In a specific embodiment, the silicon-carbon negative electrode material includes at least one of nanosilicon (Si), silicon oxide (SiO x (0 < x < 2)), and silicon-carbon.
[0058] In the present invention, the battery cell further comprises a separator, and the separator is a separator prepared by a conventional preparation method in the art or a separator obtained by commercial purchase.
[0059] In the present invention, the preparation method of the lithium-ion battery is as follows: stacking the prepared positive electrode sheet, separator, and negative electrode sheet in order, ensuring that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then obtaining a bare cell without liquid injection by winding; placing the bare cell in an outer packaging foil aluminum-plastic film, injecting the prepared electrolyte into the dried bare cell, and obtaining the desired lithium-ion battery through vacuum packaging, standing, forming, shaping, sorting and other processes.
[0060] A second aspect of the present invention provides an electrochemical device, wherein the electrochemical device comprises the lithium ion battery according to the first aspect of the present invention.
[0061] The use of the electrochemical device of the present invention is not particularly limited, and can be used for various known uses, such as laptop computers, pen-type computers, mobile computers, electronic book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, electric tools, flashlights, cameras, large household batteries or lithium ion capacitors, etc.
[0062] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0063] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0064] Example 1
[0065] The lithium ion battery of the present invention is obtained by the following method, see Table 1 for details:
[0066] (1) Preparation of positive electrode
[0067] Layered lithium composite oxide LiCoO4, polyvinylidene fluoride (PVDF), conductive carbon black SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 97.2:1:1.3:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain the desired positive electrode sheet.
[0068] (2) Negative electrode preparation
[0069] Artificial graphite, silicon carbon (with an average particle size of X1=10μm), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) are mixed in a mass ratio of 79.5:15:2.5:1.5:1:0.5, and deionized water is added to obtain a negative electrode active material under the action of a vacuum mixer; the negative electrode active material is uniformly coated on both surfaces of a copper foil; the coated copper foil is dried at room temperature, and then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain a negative electrode sheet with a thickness of 70mm; wherein, the mass content of element Si in the negative electrode active material of the negative electrode sheet is measured to account for X4wt%=10wt%.
[0070] (3) Preparation of electrolyte
[0071] In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), EC / PC / PP / EP are mixed in a mass ratio of 10 / 15 / 55 / 20, and then 15wt% of lithium hexafluorophosphate (LiPF6) based on the total mass content of the electrolyte is quickly added as a lithium salt. After dissolution, 2wt% of additive A (Formula (1-2)) based on the total mass content of the electrolyte, 15wt% of fluoroethylene carbonate (FEC), 0.5wt% of lithium difluorophosphate, 2wt% of 1,3-propane sultone (PS), 2.5wt% of 1,3,6-hexanetricarbonitrile (HTCN), 2wt% of adiponitrile (ADN), and 1wt% of succinonitrile are added. The mixture is stirred evenly, and the desired electrolyte is obtained after passing the moisture and free acid tests.
[0072] (4) Preparation of batteries
[0073] The positive electrode sheet of step 1), the negative electrode sheet of step 2) and the separator (8 μm thick polyethylene separator) are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery core; the battery core is placed in a formed outer packaging aluminum-plastic film (the outer packaging aluminum foil is placed under the punching die, and after the punching parameters are set, the convex film is lowered and combined with the concave die to be punched to successfully form the aluminum-plastic film, wherein the aluminum-plastic film includes a second polymer layer nylon layer, an aluminum layer and a first polymer layer polypropylene layer, the thickness of the nylon layer is 25 μm, the thickness of the aluminum layer is 40 μm, and the thickness of the polypropylene layer is 45 μm. The concave film R angle of the aluminum-plastic film obtained finally is measured by an R gauge, and the concave film R angle = 1.3 mm), the electrolyte of step 3) is injected into the outer packaging, and a lithium ion battery is obtained after vacuum packaging, standing, forming, shaping, sorting and other processes. The battery charge and discharge range of the present invention is 3.0-4.5V.
[0074] Example 2 Group
[0075] The second embodiment was carried out in accordance with the first embodiment, except that the average particle size of the silicon-carbon negative electrode material was changed to 1 μm and the concave film R angle of the aluminum-plastic film was changed to 2 mm. For details, see Table 1.
[0076] Example 3 Group
[0077] Example 3 was carried out with reference to Example 1, except that the type of additive A was changed, specifically:
[0078] Example 3-1, changing the type of additive A to formula (1-1);
[0079] Example 3-2, changing the type of additive A to formula (1-3);
[0080] In Example 3-3, the type of additive A is changed to formula (1-4).
[0081] Example 4 Group
[0082] Example 4 was carried out in accordance with Example 1, except that the amount of additive A was changed by X3 wt%, specifically:
[0083] Example 4-1, the addition amount of additive A was changed from X3 wt% to 0.5 wt%;
[0084] Example 4-2, the addition amount of additive A was changed from X3 wt% to 3.5 wt%;
[0085] Example 4-3, the addition amount of additive A was changed from X3 wt% to 6 wt%;
[0086] Example 4-4, changing the addition amount of additive A from X3 wt% to 8wt%;
[0087] In Example 4-5, the addition amount of additive A was changed from X3 wt% to 0 wt%.
[0088] Example 5 Group
[0089] Example 5 was carried out in accordance with Example 1, except that the mass content of element Si in the negative electrode active material was changed to X4 wt%, specifically:
[0090] Example 5-1, changing the mass content of element Si in the negative electrode active material from X4 wt% to 0.5wt%;
[0091] Example 5-2, changing the mass content of element Si in the negative electrode active material from X4 wt% to 20wt%;
[0092] Example 5-3, changing the mass content of element Si in the negative electrode active material from X4 wt% to 30wt%;
[0093] In Example 5-4, the mass content of element Si in the negative electrode active material was changed from X4 wt % to 35 wt %.
[0094] Example 6
[0095] Example 6 is carried out with reference to Example 1, with the only difference being that the thicknesses of the nylon layer, the aluminum layer and the polypropylene layer of the aluminum-plastic film are changed, the thickness of the nylon layer is 35 μm, the thickness of the aluminum layer is 30 μm, and the thickness of the polypropylene layer is 55 μm.
[0096] Example 7
[0097] Example 7 was carried out with reference to Example 1, except that the additive lithium difluorophosphate was not added during the preparation of the electrolyte.
[0098] Example 8
[0099] Example 8 was carried out with reference to Example 1, with the only difference being that, during the preparation of the electrolyte, the mass content of the additive fluoroethylene carbonate added was 3 wt %.
[0100] Comparative Example 1
[0101] The comparative example 1 group was carried out with reference to the example 1, except that the average particle size of the silicon-carbon negative electrode material was changed to 1 μm and the concave film R angle of the aluminum-plastic film was changed to 2 mm. For details, see Table 1.
[0102] Comparative Example 2
[0103] Comparative Example 2 was carried out with reference to Example 1, except that the addition amount of additive A was changed from X3 wt% to 0wt%, and the average particle size of the silicon-carbon negative electrode material was changed from X1 μm to X2 mm, as shown in Table 1.
[0104] Table 1
[0105]
[0106]
[0107] Lithium-ion battery test example
[0108] The lithium ion batteries obtained in the above examples and comparative examples were tested by the following method, and the test results are recorded in Table 2:
[0109] The test methods for performance parameters are as follows:
[0110] (1) Cycle test of lithium-ion batteries at 25°C
[0111] The battery cell was placed at 25°C, charged at 1C constant current to the upper voltage limit (4.5V), then charged at 4.5V constant voltage to 0.05C, and left to stand for 5 minutes; then discharged at 0.5C constant current to 3V, and left to stand for 5 minutes. This is a charge and discharge cycle. After charging / discharging in this way, the capacity retention rate / % of the lithium-ion battery after 1000T cycle is recorded, and the results are recorded in Table 2.
[0112] (2) 25℃ Cyclic Expansion Test:
[0113] The battery cell is charged to 3.8V at a constant current of 1.8C, and then charged to a constant voltage of 3.8V until the charging current is less than 0.05C. It is left to stand for 10 minutes. At this time, the battery cell is in a 50% SOC state. The weight of the battery cell measured by the mass measuring instrument is W Kg, and the thickness of the battery cell measured by the thickness measuring machine is Q0 mm. The cycle expansion rate of the battery cell is L x =Q x / Q0*100%, the results are recorded in Table 2.
[0114] (3) Rate charging test of lithium-ion batteries
[0115] The corresponding battery was placed in a constant temperature environment of 25℃, ① left to stand for 10min, ② first discharged to 3.0V with 0.2C, ③ left to stand for 10min, ④ charged to 4.45V at a certain rate, with a cut-off current of 0.02C, ⑤ left to stand for 10min, ⑥ discharged to 3.0V with 0.2C, ⑦ left to stand for 10min. Steps ④ to ⑦ were cycled until all rate charging tests were completed, with a charging rate of 3C, and then the constant current charging ratios of different charging rates were collected, constant current charging ratio = constant current charging capacity ÷ charging capacity × 100%, see Table 2.
[0116] Table 2
[0117]
[0118]
[0119] From the analysis of Table 2, it can be seen that the present invention adjusts the R angle of the concave film of the aluminum-plastic film to match the silicon-carbon negative electrode material with a suitable particle size, thereby reducing the risk of easy deformation of the battery in the later stage of the cycle due to the high expansion characteristics of the silicon negative electrode, and improving the long-cycle expansion performance and cycle stability of the lithium-ion battery; adding additive A to the negative electrode system blended with the silicon-carbon negative electrode material can improve the interface stability of the silicon-carbon negative electrode material, thereby further improving the long-cycle stability of the silicon negative electrode, and can help to improve the fast charging capability and rate performance of the lithium-ion battery.
[0120] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: It comprises a battery core and an aluminum-plastic film coated on the outside of the battery core; the battery core comprises a negative electrode, the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon negative electrode material; The average particle size of the silicon-carbon negative electrode material is X1 μm, 5 μm≤X1 μm≤15 μm; The concave film R angle of the aluminum-plastic film is X2 mm, 0.01 mm ≤ X2 mm ≤ 3 mm; Among them, 0.05≤X2 / X1≤0.
15.
2. The lithium-ion battery according to claim 1, characterized in that 0.07≤X2 / X1≤0.12; and / or, 7μm≤X1μm≤12μm; and / or, 0.7mm≤X2 mm≤1.3mm.
3. The lithium ion battery according to claim 1 or 2, characterized in that: The lithium-ion battery further comprises an electrolyte, wherein the electrolyte comprises an additive A, and the structural formula of the additive A is shown in formula (1): wherein n is 1-3, and R is independently selected from halogen, substituted or unsubstituted C1-C3 alkyl, and when substituted, the substituent of the C1-C3 alkyl is halogen; Preferably, the substituent of the C1-C3 alkyl group is F.
4. The lithium-ion battery according to claim 3, characterized in that: The additive A comprises at least one of the following compounds; 5. The lithium-ion battery according to claim 3, characterized in that: Based on the total mass of the electrolyte, the mass content of the additive A is X3 wt%, 0.5 wt%≤X3 wt%≤6 wt%; And / or, the mass content of element Si in the negative electrode active material is X4 wt%, 0.5 wt%≤X4 wt%≤30 wt%; Preferably, 0.07≤X3 / X4≤0.
55.
6. The lithium-ion battery according to claim 5, characterized in that: 0.7wt%≤X3wt%≤3wt%; and / or, 5wt%≤X4wt%≤30wt%; and / or, 0.08≤X3 / X4≤0.
2.
7. The lithium-ion battery according to claim 1, characterized in that: The aluminum-plastic film comprises a first polymer layer close to the battery core, a second polymer layer away from the battery core, and an aluminum layer located between the first polymer layer and the second polymer layer; Preferably, the first polymer layer comprises a polypropylene compound; Preferably, the second polymer layer comprises a polyamide compound; Preferably, the thickness of the second polymer layer is 20 μm-30 μm; and / or the thickness of the aluminum layer is 35 μm-45 μm; and / or the thickness of the first polymer layer is 40 μm-50 μm.
8. The lithium ion battery according to claim 3, characterized in that: The electrolyte also includes lithium difluorophosphate; And / or, the electrolyte further comprises fluoroethylene carbonate; Preferably, based on the total mass of the electrolyte, the mass content of the lithium difluorophosphate is 0.1wt%-1wt%; Preferably, based on the total mass of the electrolyte, the mass content of the fluoroethylene carbonate is 7wt%-20wt%.
9. The lithium-ion battery according to claim 1, characterized in that: The thickness of the negative electrode plate is 45mm-80mm.
10. An electrochemical device, characterized in that: The electrochemical device comprises the lithium ion battery according to any one of claims 1 to 9.
Citation Information
Cited By
Battery monomer, battery device and energy storage device
CN121507092A